Measurement of digital video broadcasting-terestrial (DVB-T) signal in Malaysia / Tarmimi Sahad - Sahad, Tarmimi
This paper presents analysis of measurement results of DVB-T (Digital Video Broadcasting Terrestrial) signals in Malaysia. In this project, a measuring vehicle equipped with measuring equipment and a receiving antenna (directional) which is placed at height of 10m above ground level was used. Parameters quality of DVB-T; field strength, MER (Modulation Error Rate), BER (Bit Error Rate) before Viterbi and BER after Viterbi for 100 test points in the coverage area is investigated and analyzed. Measurement shows 99% of the test point received a good DVB-T signal quality (reception possible).